2018
DOI: 10.3892/mmr.2018.9344
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑376a inhibits cell proliferation and invasion in osteosarcoma via directly targeting SATB1

Abstract: Aberrantly expressed microRNAs (miRs) are implicated in the regulation of osteosarcoma (OS) onset and development. Therefore, key miRs in OS must be identified to develop promising and effective therapeutic targets for patients with OS. In the present study, reverse transcription‑quantitative polymerase chain reaction analysis revealed that miR‑376a‑3p expression was downregulated in OS tissues and cell lines. Additionally, decreased miR‑376a expression was associated with tumor size and lymph node infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“… 29–32 miR-376a-3p, induced by TTN-AS1, mitigates the effects on colorectal cancer cell proliferation and invasion, which is a target of TTN-AS1, 33 miR-376a-3p mitigates the development of glioma by negatively regulating KLF15. 34 In addition, miR-376a-3p inhibits cell proliferation and invasion of osteosarcoma cells by directly targeting SATB1 35 In the present study, we confirmed that miR-376a-3p could affect the function of AML cells by regulating MT1X at the cellular level. Our results revealed that overexpression of miR-376a-3p evidently inhibited the proliferation, arrested in the G0/G1 phase and induced apoptosis of AML cells, and its suppressive effect could be reversed when MT1X was overexpressed, which were consistent with the trend of miR-376a-3p effects in other tumors.…”
Section: Discussionsupporting
confidence: 67%
“… 29–32 miR-376a-3p, induced by TTN-AS1, mitigates the effects on colorectal cancer cell proliferation and invasion, which is a target of TTN-AS1, 33 miR-376a-3p mitigates the development of glioma by negatively regulating KLF15. 34 In addition, miR-376a-3p inhibits cell proliferation and invasion of osteosarcoma cells by directly targeting SATB1 35 In the present study, we confirmed that miR-376a-3p could affect the function of AML cells by regulating MT1X at the cellular level. Our results revealed that overexpression of miR-376a-3p evidently inhibited the proliferation, arrested in the G0/G1 phase and induced apoptosis of AML cells, and its suppressive effect could be reversed when MT1X was overexpressed, which were consistent with the trend of miR-376a-3p effects in other tumors.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, we focused our attention on MAPK6. Previous reports have found that MAPK6 plays an important role in many tumors [40][41][42][43]. We found that knockdown of ZNF671 up-regulated the expression level of MAPK6.…”
Section: Discussionsupporting
confidence: 51%
“…In a recent study, Hegazy et al [9] stated that the advancement of LSCC is influenced by the alteration of miRNA expression. In particular, laryngeal cancer cells show downregulation of miR-138, which leads to less apoptosis and more cell proliferation [78]. Other miRNAs that play a relevant role in the development of laryngeal cancer (LC) are miR-195-5p and miR-206 [79].…”
Section: The Emerging Role Of Lncrnas Mirnas and Mrnasmentioning
confidence: 99%